2023
DOI: 10.1182/blood.2022018152
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Asian-type DEL can safely be transfused using RhD-positive blood

Abstract: Red blood cells (RBCs) of the Asian-type DEL phenotype express few RhD proteins and are typed as serologic RhD-negative (D-) in routine testing. RhD-positive (D+) RBC transfusion for Asian-type DEL patients has been proposed but has not been generally adopted due to a lack of direct evidence regarding its safety and underlying mechanism. We performed a single-arm multicenter clinical trial to document the outcome of D+ RBC transfusion in Asian-type DEL patients; none of the recipients (0/42; 95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Possibly, our findings also can be transferred to patients with Asian type Del, who appear to be RHDnegative by serologic testing but also have a C in their RHCE-phenotype 24 and safely can be transfused with RHD-positive RBCs. 25 However, due to our study population, our findings are firstly limited to patients of Caucasian origin.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, our findings also can be transferred to patients with Asian type Del, who appear to be RHDnegative by serologic testing but also have a C in their RHCE-phenotype 24 and safely can be transfused with RHD-positive RBCs. 25 However, due to our study population, our findings are firstly limited to patients of Caucasian origin.…”
Section: Discussionmentioning
confidence: 99%
“…29 RHD(1227G>A) expresses a very weak D antigen with the complete repertoire of D antigen epitopes, which indicates that Asian-type DEL recipients may not develop alloanti-D after exposure to RhD-positive RBCs. 12 Although some retrospective studies indicated that no alloantibodies against RBC antigens were identified in cases of pregnancy with RHD(1227G>A), [30][31][32] those women are routinely managed as RHD*01N.01 individuals in most Chinese hospitals. Takahashi et al 16 explored an RHD genotyping method based on amplicon-sequencing and correctly predicted fetal RHD genotyping for eight RhD-negative pregnant women, including three pregnant women carrying RHD (1227G>A).…”
Section: Discussionmentioning
confidence: 99%
“…And based on the resolution of the molecular structure, it was predicted early on that Asian‐type DEL recipients “might not even develop anti‐D after exposure to regular” RhD‐positive red cells. “Because of the sheer number of patients and of blood units involved, this topic could considerably affect—and might ease—transfusion practice in East Asian populations.” 17 These predictions have since been confirmed by many studies and their clinical advantages are now becoming widely implemented in clinical practice for Asian‐type DEL 14 . In contrast, some other DEL variants are categorized as partial and lack one or more D‐epitopes, making them prone to develop anti‐D if exposed to regular RhD‐positive red cells 6,8 …”
mentioning
confidence: 93%
“…17 These predictions have since been confirmed by many studies and their clinical advantages are now becoming widely implemented in clinical practice for Asian-type DEL. 14 In contrast, some other DEL variants are categorized as partial and lack one or more D-epitopes, making them prone to develop anti-D if exposed to regular RhDpositive red cells. 6,8 Various HLA alleles have been reported to increase or decrease red cell alloimmunization.…”
mentioning
confidence: 99%
See 1 more Smart Citation